CRIMINALITY IN LATGALE IN THE REFLECTION OF THE NEWSPAPER “LATGOLAS WÒRDS” (1919–1921) - Strods, Kaspars (Via Latgalica, 2018)
After the end of the Latvian War of Liberation (1918–1920) and the liberation of Latgale from the Bolsheviks, everyday life started to improve gradually, however, due to various objective circumstances (the geographical position – the border with the Soviet Russia, the presence of various criminal elements, relocation of refugees and several socio-economic factors such as unemployment, poverty, etc.), the region was still highly criminal. Processes and events including criminal offenses occurring in the territory of Latvia were reflected in various state and regional newspapers. The largest regional newspaper was “Latgolas Wòrds”, published by the Latgalian Christian Farmers’ Union, which eventually became an independent source of information for a large part of the population of Latgale. The aim of the study is to identify the main trends of criminality in the territory of Latgale as reflected in the newspaper “Latgolas Wòrds” (1921–1921). The content of publications under analysis indicates that there were various crimes committed (including murder, robbery, theft, etc.); the selected publications also reveal the overall socio-economic situation in the region during this period. The rapid spread of crime in the rural areas testifies to the socio-economic problems experienced by the population of Latgale (unemployment, devastated farms, the overall food deficit, etc.). Similarly, the publications outline the social portrait of criminals: among them there were socially disadvantaged people (rural population, etc.) and servicemen of different armies. Active or passive participation of certain social groups (soldiers, police officers, etc.) in committing crimes indicates not only certain problems in the activities of the Latgalian security institutions, but also in the general trends typical of the Latvian state on the whole. It should be noted that the news displayed in the newspaper can hardly be perceived as an opinion of the general public, but rather as an interpretation of events by a certain group or its representatives.